Avaliação do papel das mudanças curriculares (ENEM 2009) e das novas Diretrizes Curriculares Nacionais na perspectiva de aprendizagem entre professores de matemática - Silivera, Josilda da Cruz (2016)
The National Secondary Education Examination (ENEM) was established in 1998 aiming to be a diagnostic evaluation primarily to assess students and high school courses, and over the years has been taking the place of traditional entrance exam of Federal Institutions of the country's Higher Education and allowing the federal government to develop public policies for basic education. Soon after, in 2009, it was established the 2009 ESMS (also known as New ESMS) establishing a new proposal for the high school, and then in 2012 the New National Curriculum Guidelines for Secondary Education (NDCNEM) they are instituted. This interim the following research problem arose: What is the role of curriculum changes arising from the Proposal of the 2009 ENEM and NDCNEM in the learning process, from the perspective of mathematics teachers from a high school school in the city of Maranguape (EC)? From this problem was elaborated this work in order to evaluate the role curricular changes arising from the 2009 ENEM proposal and NDCNEM in the learning process, from the perspective of mathematics teachers from a school in the city of Maranguape (EC) . As for the approach, the research is qualitative,referring to the goals it is exploratory and explanatory and on the procedures to be treated as field research. The data collection instrument was the interview with structured questionnaire applied to mathematics teachers from a high school school Public Network Maranguape. Given the above we sought to address the perspective of teachers and the curriculum changes which thereby made the ENEM 2009 and NDCNEM. The analysis of this study was performed using the method of content analysis suggested by Bardin author, based on the concept of evaluation of author Ralph Tyler and contributions from other authors, such as Luckesi, Dewey, Rabelo and Sacristan. In addition, it is noted that the study procedures were submitted for review by the Ethics Committee of the Federal University of Ceará.